Correction: A rapid multiplex PCR assay for presumptive species identification of rhinoceros horns and its implementation in Vietnam. - Kyle M Ewart; Greta J Frankham; Ross McEwing; Dang Tat The; Carolyn J Hogg; Claire Wade; Nathan Lo; Rebecca N Johnson (PLoS ONE, 2018)
[This corrects the article DOI: 10.1371/journal.pone.0198565.].